New dual purpose maize cultivars with quality stover traits for India - CGIAR Research Program on Livestock (2021)
The results were published in 2021 in Nature Scientific Reports, and will allow maize breeders to select for stover quality traits more quickly and cost-effectively, and to develop new dual purpose maize varieties without sacrificing grain yield.